Optimization of Rhizopus spp. Production as Mycoprotein using Soymilk Media - Dani Muliawan Halim; Anastasia Tatik Hartanti; Stephanie (Microbiology Indonesia, 2022)
Mycoprotein is food with high protein content, fiber, and low in cholesterol made from fungal mycelium. In this research, mycoprotein was produced by spp. isolated fr Rhizopus om tempeh with soymilk as growth media. This research aims to determine the best strain of spp. and op Rhizopus timum carbon to nitrogen ratio for mycoprotein production Two parameters were applied which w . ere inoculum selection and carbon to nitrogen ratio treatment in media. The best inoculum was selected from four strains of Rhizopus spp., ATH 1,ATH 24,ATHÂ  40, and ATH 53. On the other hand, carbon to nitrogen ratio treatment used were as follows 20:1, 20:2, and 40:2. Mycelium dry weight and protein content were measured, as well as reduction sugar, dissolved protein and total volatile base nitrogen concentration in media. The best strain for producing biomass was ATH 24 with 0.6 g of 0 mycelium dry weight per 50 mL of media and the protein content was 0.236 g. The best carbon to nitrogen ratio treatment was 20:1 with 0.57 gram of mycelium dry weight per 50 mLof media and the protein content was 0.20 g. Thus, our data indicate that strain ATH 24 with 20:1 of carbon to nitrogen ratio in media were highly potential for producing mycoprotein. Keywords: fermentation, mycelium, mycoprotein, Rhizopus, soymilk